Environmental pharmacology—Dosing the environment: IUPHAR review 36. (16th August 2022) - Connolly, Christopher N.; Alexander, Stephen P. H.; Davies, Jamie A.; Spedding, Michael
Abstract : Pesticide action is predominantly measured as a toxicological outcome, with pharmacological impact of sublethal doses on bystander species left largely undocumented. Likewise, chronic exposure, which often results in responses different from acute administration, has also been understudied. In this article, we propose the application of standard pharmacological principles, already used to establish safe clinical dosing regimens in humans, to the 'dosing of the environment'. These principles include relating the steady state dose of an agent to its beneficial effects (e.g. pest control), while minimising harmful impacts (e.g. off‐target bioactivity in beneficial insects). We propose the term 'environmental therapeutic window', analogous to that used in mammalian pharmacology, to guide risk assessment. To make pharmacological terms practically useful to environmental protection, quantitative data on pesticide action need to be made available in a freely accessible database, which should include toxicological and pharmacological impacts on both target and off‐target species.